2000
DOI: 10.1074/jbc.m910145199
|View full text |Cite
|
Sign up to set email alerts
|

Virus Maturation Targets the Protein Capsid to Concerted Disassembly and Unfolding

Abstract: Many animal viruses undergo post-assembly proteolytic cleavage that is required for infectivity. The role of maturation cleavage on Flock House virus was evaluated by comparing wild type (wt) and cleavage-defective mutant (D75N) Flock House virus virus-like particles. A concerted dissociation and unfolding of the mature wt particle was observed under treatment by urea, whereas the cleavage-defective mutant dissociated to folded subunits as determined by steady-state and dynamic fluorescence spectroscopy, circu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 42 publications
0
28
0
Order By: Relevance
“…We also found that the coat proteins remain bound to the nucleic acid after pressure disassembly of the capsid in comoviruses (26,55), picornaviruses (56), and nodaviruses (27), suggesting again the strong interactions between protein and nucleic acid in virus assembly. These interactions can be disrupted by decreasing temperature to negative values (Ϫ15°C) under pressure, revealing their entropic nature (26).…”
Section: Discussionmentioning
confidence: 83%
“…We also found that the coat proteins remain bound to the nucleic acid after pressure disassembly of the capsid in comoviruses (26,55), picornaviruses (56), and nodaviruses (27), suggesting again the strong interactions between protein and nucleic acid in virus assembly. These interactions can be disrupted by decreasing temperature to negative values (Ϫ15°C) under pressure, revealing their entropic nature (26).…”
Section: Discussionmentioning
confidence: 83%
“…Recently we found that the maturation/ cleavage of flock house virus capsid converts the coat protein into a metastable conformation, whereas a cleavage-defective mutant particle coat protein reversibly reassembles into particles. The mature capsid is more sensitive to pressure than the cleavage-defective, immature particle (42).…”
Section: Fig 3 Pressure Effects On Sindbis and Influenza Virusesmentioning
confidence: 99%
“…This change makes it sensitive to both pH and pressure. Cavities have been implicated in protein metastability in several systems (32,(41)(42)(43). The influenza virus system has the unique property of having a water-penetrated cavity in the precursor protein, which eliminates water on proteolytic cleavage, originating the pH and pressure sensitivity.…”
Section: Fig 3 Pressure Effects On Sindbis and Influenza Virusesmentioning
confidence: 99%
“…Metastability has been observed for serine protease inhibitors (40,41), heat shock transcription factors (42), viral envelope glycoproteins (43), and proteolitically processed capsid proteins of nonenveloped viruses (11). Here, we characterize the metastable state of the ribonucleoprotein capsid by perturbing it with hydrostatic pressure or urea.…”
mentioning
confidence: 99%
“…Enveloped viruses enter cells by protein-mediated fusion of the membrane enclosing the virus particle with the cellular membrane, which ultimately results in release of the nucleocapsid into the cell for processing (3). In nonenveloped viruses, biophysical studies have been carried out to understand how the overall stability depends on protein-protein interactions (4 -7), protein-nucleic acid interactions (8,9), and proteolysis maturation (10,11). Here, the alphavirus Mayaro was used as a simple model of enveloped viruses to compare the properties of the whole and nucleocapsid particles deprived of the lipid bilayer and transmembrane glycoproteins.…”
mentioning
confidence: 99%